Analisis Pengelompokan Data Argumen Tentang Penerapan Kebijakan Sistem Zonasi Pada Pendaftaran Sekolah Dengan Menggunakan Metode Clustering - Ika Pusvitaningrum Ika (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2020)
The Indonesian government has taken steps to seek comprehensive reform of schools. One of the efforts of governments is to implement a zoning system, which, in this policy, governments have set boundaries - the limit of rayon to the region around schools, which, in turn, should be prioritized for new student registrations, those of which live closer to school. Beyond rayon or school district can register with the old person's accomplishments and transmigration pathways, which is a factor in the rise of controversy in society. By doing so, these studies can become a valid standard or standard for schools to prepare for the zoning system for the New Year. In this study the data used is the real data obtained from the dissemination of the questionnaire to society. The data gathered is 380 and 181 male respondents and 199 female respondents of 2 district in pati, the margoyoso and tayu districts. Data is processed using version 1. 1,456 r software, and it is thereafter done clustering by k-means.